PENERAPAN METODE TOPSIS DALAM SISTEM PENGAMBILAN KEPUTUSAN PEMBERIAN BANTUAN REHABILITASI RUMAH - Letelay, Kornelis; Mola, Sebastianus A.S; Snae, Derwinta Pondence (Universitas Muria Kudus, 2023)
The provision of assistance for the rehabilitation of uninhabitable houses to the community often results in fraud and errors in the process of selecting and providing assistance. The TOPSIS method is a method used to calculate in the decision-making process in determining prospective recipients of uninhabitable housing rehabilitation assistance. The results of the TOPSIS calculation from the system were then tested using the sensitivity test method by giving a weight change of 0.5 and 1 for each criterion weight. The test results in 2019 with a total of 25 families of data obtained the most sensitive criteria for adding a weight of 0.5, namely the criteria for work and life dependents with a percentage result of 92%, while for adding weight to 1 the most sensitive criterion is the job criteria with a percentage result of 96%. Black box testing of the system built is measured using a questionnaire media with 10 statement items given to 15 respondents which is calculated using a Likert Scale where the system built is highly approved which can be seen from the index percentage value greater than 80% (strongly agree).